Impacts of shading on flower formation and longevity, leaf chlorophyll and growth of bougainvillea glabra - Saifuddin, M.; Osman, Normaniza; Hossain, A.M.B.S. (Asian Network for Scientific Information, 2010)
Bougainvillea plants were exposed to artificially reduced light intensity to capture different Photosynthetic Photon Flux Density (PPFD), 0% (direct sunlight), 30, 50 and 75% shading and to observe the effects of shading on flower formation and longevity, leaf chlorophyll and sugar content and quality of plants. Plant attained the greatest leaf size with maximum branching when seedlings were grown in 30 and 50% shading, whereas 0% shading showed the lowest value. Growth parameters related to the plant characteristics such as branch initiation, branch growth and potassium content increased under high shading treatments. Plants exposed to 0% shade showed the highest sugar content and the sugar content decreased by increasing shading. The low light intensity that results in decreased sugar and chlorophyll contents may be attributed to the reduction of flower initiation and in turn to the acceleration of flower abscission. In addition, more than 30% shading led to stop up flower initiation completely. Hence, it is suggested that 0% shading can be applied to maintain frequent flower initiation and flower longevity. © 2010 Asian Network for Scientific Information.